2005
DOI: 10.1352/0895-8017(2005)110[405:daoesa]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive Analysis of Epileptic Seizures and Problem Behavior in Adults With Developmental Disabilities

Abstract: We studied possible relations between seizures and problem behavior in 3 adults with developmental disabilities. Each person was observed for between 56 and 92 days to record occurrences of seizures and problem behavior. Results of our descriptive analysis indicated an association between seizures and problem behavior for each participant. For Stan, most problem behavior occurred following absence seizures. For Tom, problem behaviors only occurred before tonic-clonic seizures but showed no relation to absence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Physical distress caused by non-psychiatric medical problems can provoke changes in mood and behaviour in people with ID (Carr & Owen-Deschryer 2007;Nikolov 2008). Health problems identified as causing or worsening behaviour problems in this population are various, ranging from ear infections, premenstrual pain, sleep disturbances and allergies, to dental pain, seizures and Gastrointestinal (GI) distress (Gunsett et al 1989;Kennedy & Meyer 1996;Bosch et al 1997;O'Reilly 1997;Bohmer et al 2001;Carr et al 2003;Molloy & Manning-Courtney 2003;Roberts et al 2005;Kennedy et al 2007;Mathews et al 2008). In behavioural terms, feeling ill, in pain or generally distressed because of a physical problem [i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Physical distress caused by non-psychiatric medical problems can provoke changes in mood and behaviour in people with ID (Carr & Owen-Deschryer 2007;Nikolov 2008). Health problems identified as causing or worsening behaviour problems in this population are various, ranging from ear infections, premenstrual pain, sleep disturbances and allergies, to dental pain, seizures and Gastrointestinal (GI) distress (Gunsett et al 1989;Kennedy & Meyer 1996;Bosch et al 1997;O'Reilly 1997;Bohmer et al 2001;Carr et al 2003;Molloy & Manning-Courtney 2003;Roberts et al 2005;Kennedy et al 2007;Mathews et al 2008). In behavioural terms, feeling ill, in pain or generally distressed because of a physical problem [i.e.…”
Section: Introductionmentioning
confidence: 99%
“…There is a lack of knowledge regarding the causal mechanisms that underlie the observed relationship between epilepsy and challenging behavior. Roberts, Yoder, and Kennedy (2005) demonstrated that epileptic seizures experienced by three individuals were temporally associated with the occurrence of challenging behavior as recorded by care staff. The interaction between seizure occurrence and environmental events was not assessed; therefore, it is unclear whether seizures functioned as a motivating operation or by some other behavioral mechanism.…”
Section: Epilepsymentioning
confidence: 95%
“…Psychiatric and medical diagnoses are generally more difficult to establish in PWID with lower functional levels, secondary to limited social skills, limited verbal communication, potential presence of behavioural problems and environmental factors (Deb and Hunter, 1991;Roberts et al, 2005;Smith and Matson, 2010). Traditional methods of assessing psychiatric disorders rely on self-reporting, interviews and behavioural observations (Smith and Matson, 2010).…”
Section: Behaviour Change In People With Intellectual Disabilities (Pmentioning
confidence: 99%